2010
DOI: 10.1007/s00454-009-9240-9
|View full text |Cite
|
Sign up to set email alerts
|

Approximating the Pathway Axis and the Persistence Diagrams for a Collection of Balls in 3-Space

Abstract: Given a collection B of balls in a three-dimensional space, we wish to explore the cavities, voids, and tunnels in the complement space of B. We introduce the pathway axis of B as a useful subset of the medial axis of the complement of B and prove that it satisfies several desirable geometric properties. We present an algorithm that constructs the pathway graph of B, a piecewise-linear approximation of the pathway axis. At the heart of our approach is an approximation scheme that constructs a collection K of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(57 reference statements)
1
2
0
Order By: Relevance
“…We should mention here, that a similar concept called topological persistence and simplification was proposed by Edelsbrunner et al [ELZ02], but the lifetime of a cavity is measured differently. Perhaps the lifetime proposed by Yaffe et al [YH10] is more close to the approach proposed in this paper.…”
Section: Cavities Hierarchysupporting
confidence: 73%
See 1 more Smart Citation
“…We should mention here, that a similar concept called topological persistence and simplification was proposed by Edelsbrunner et al [ELZ02], but the lifetime of a cavity is measured differently. Perhaps the lifetime proposed by Yaffe et al [YH10] is more close to the approach proposed in this paper.…”
Section: Cavities Hierarchysupporting
confidence: 73%
“…Yaffe and Halperin came up with an idea to approximate larger balls by a number of balls having the same size as the smallest ball [YH10]. Thanks to this approximation, they can still use the ordinary Voronoi diagram.…”
Section: Related Workmentioning
confidence: 99%
“…In 2007, Kozlikova et al also reported an idea of tunnel extraction using the ordinary Voronoi diagram of atom center points and the Delaunay triangulation [15]. In 2008, Yaffe et al reported a method using the alphashape (which is a derivative structure of the ordinary Voronoi diagram of points) and developed the software MolAxis [16], [17], [18] which attempted to reflect the size differences among different atom types by an approximation with a number of identically sized balls (thus this approach inevitably produced an approximated solution). In 2008, Ho and Gruswitz used a grid-based approach to tunnel extraction and developed a software HOLLOW [19].…”
Section: Literature Reviewmentioning
confidence: 99%